An algorithm to solve a quantile optimization problem with loss function having a separable structure, and its application to an aerospace problem. (7th July 2019) - Ivanov, S.V.; Kibzun, A.I.; Stepanova, A.S.
Abstract: A quantile minimization problem with loss function having separable structure is considered. The distribution of the random parameters is assumed to be normal. To solve the problem, the confidence method and the sample average approximation method are used. Thus, the problem is reduced to a combinatorial one, which is solved by using the variable neighborhood search. The suggested algorithm is applied to optimization of runway area. Parameters of the runway are selected to minimize the area taking into account random wind speed.